Ultrastructural characterization of GABAergic and excitatory synapses in the inferior colliculus - Nakamoto, Kyle T.; Mellott, Jeffrey G.; Killius, Jeanette; Storey-Workley, Megan E.; Sowick, Colleen S.; Schofield, Brett R. (Frontiers in Neuroanatomy, 2014)
In the inferior colliculus (IC) cells integrate inhibitory input from the brainstem and excitatory input from both the brainstem and auditory cortex. In order to understand how these inputs are integrated by IC cells identification of their synaptic arrangements is required. We used electron microscopy to characterize GABAergic synapses in the dorsal cortex, central nucleus, and lateral cortex of the IC (ICd, ICc and IClc) of guinea pigs. Throughout the IC, GABAergic synapses are characterized by pleomorphic vesicles and symmetric junctions. Comparisons of GABAergic synapses with excitatory synapses revealed differences (in some IC subdivisions) between the distributions of these synapse types onto IC cells. For excitatory cells in the IClc and ICd GABAergic synapses are biased toward the somas and large dendrites, whereas the excitatory boutons are biased toward spines and small dendrites. This arrangement could allow for strong inhibitory gating of excitatory inputs. Such differences in synaptic distributions were not observed in the ICc, where the two classes of bouton have similar distributions along the dendrites of excitatory cells. Interactions between excitatory and GABAergic inputs on the dendrites of excitatory ICc cells may be more restricted (i.e., reflecting local dendritic processing) than in the other IC subdivisions. Comparisons across IC subdivisions revealed evidence for 2 classes of GABAergic boutons, a small GABAergic (SG) class that is present throughout the IC and a large GABAergic (LG) class that is almost completely restricted to the ICc. In the ICc, LG and SG boutons differ in their targets. SG boutons contact excitatory dendritic shafts most often, but also contact excitatory spines and somas (excitatory and GABAergic). LG synapses make comparatively fewer contacts on excitatory shafts, and make comparatively more contacts on excitatory spines and on somas (excitatory and GABAergic). LG boutons likely have a lemniscal origin.